Like a Captive Bird : Gender and Virtue in Plutarch - Warren, Lunette (Book collections on Project MUSE., 2022)
Like a Captive Bird examines the use of psychagogy, a set of therapeutic principles for achieving virtue, in Plutarch's work. Warren argues that Plutarch's work makes use of moral-educational literature to inculcate a gendered sense of self in the reader, and that this self is fundamentally concerned with the sex of the body, its reproductive role, and the conjugal relationship. Psychagogy is therefore a process of self-formation which aims to regulate and distribute power in gendered interactions on the basis of virtue. On this view, virtue is not just a disposition of the soul, it is also a set of rules and regulations for how one should act and interact with others, and this ties it inextricably to gender. Plutarch furthers this view in his theoretical-philosophical work, where he moves beyond the gender binary to a psychic scale of gender expression which figures normative gender as virtuous and non-normative gender as vicious. He then examines the implications of these views in the biographies. Warren therefore holds that Plutarch's views on women and gender across all genres are ideologically coherent, even if written at different stages of his life.